Antique Traditions and Formation of Italian National Model of Self-Organization of Scientific Community - R. O. Raynkhardt (Научный диалог)
The origins of the formation of the Italian model of self-organization of the scientific community and their perception by Italian scientists are covered. In the course of critical analysis the contentious issues of mapping the early stages of development of Italian science with the traditions of the Pythagoreans are revealed, which, in turn, has had a significant influence on the work of the Athenian Academy of Plato. Attention is drawn to such peculiarities of the Pythagorean Union as its secret nature (a contradiction to the ideals of transparency and openness), the lack of reliable primary sources describing his existence, the existence of contradictory and somewhat unflattering legends around the Pythagoreans. On the other hand, positive characteristics are noted that justify the consideration of the Academy of Plato as the source of origin the scientific community, such as a form of training - a dialogue between teachers and students, the transition to the latter to the first category during the accumulation of knowledge and experience, the presence of the head (scholarch), democracy in respect of the admission of new members, formal lack of property and sex qualifications. The novelty of the study lies in identifying and justifying the fact that from the point of view of institutional self-organizing community the modern Italian research personnel perceive themselves as successors of the traditions of the Academy of Plato, raising to it their roots. It is proved that the cultivation of this concept plays an important role in education of modern Italy and to a large extent forms self-identification of young scientists.